Polymer nitric oxide donors potentiate the treatment of experimental solid tumours by increasing drug accumulation in the tumour tissue - Studenovsky, M; Sivak, L; Sedlacek, O; Konefal, R; Horkova, V; Etrych, T; Kovar, M; Rihova, B; Sirova, M (Journal of controlled release, 2018)
The delivery of nitric oxide (NO) specifically to solid tumours was explored in this study as a strategy to augment the passive accumulation of nanomedicines in tumours induced by the Enhanced Permeability and Retention (EPR) effect. An increase in accumulation was achieved by the binding of the chemical precursor of NO, based on an organic nitrate, to a water-soluble synthetic polymer drug carrier. Four structurally different N-(2-hydroxypropyl)methacrylamide (HPMA)-based polymer NO donors were synthesized. Depending on their chemical structure, two of these donors were hydrolytically stable, while two rapidly released the parent nitrate under acidic conditions, mimicking the intracellular environment. The polymer NO donors were shown to overcome the drawbacks related to low-molecular-weight NO releasing compounds, namely systemic toxicity, lack of site specificity, and fast blood clearance. The NO donors showed intracellular NO release upon incubation with tumour cells. In vivo, they potentiated the EPR effect, resulting in an increased accumulation of polymer-bound cytotoxic drug doxorubicin (Dox) in EL4 T-cell lymphoma inoculated in mice. This led to a better therapeutic outcome in the treatment of lymphoma with the high-molecular-weight polymer conjugates carrying Dox but not in the treatment with the free Dox. The localized augmentation of the EPR effect via the tumour-specific NO delivery system can be viewed as a promising strategy to potentiate polymer-based tumour therapy without increasing systemic toxicity.
Keywords: Lymphoma, T-Cell; Animals; Doxorubicin; Female; buněčné linie; protinádorová antibiotika; ženské pohlaví; Drug Carriers; Polymers; lidé; Antibiotics, Antineoplastic; Cell Line; Nitric Oxide Donors; lymfom T-buněčný; Drug Synergism; doxorubicin; polymery; synergismus léků; nosiče léků; donory oxidu dusnatého; zvířata; Mice, Inbred C57BL; myši inbrední C57BL; Humans